Divergent responses to SARS-CoV-2 infection in bronchial epithelium with pre-existing respiratory diseases - Justine Oliva; Manon Ruffin; Claire Calmel; Aurélien Gibeaud; Andrés Pizzorno; Clémence Gaudin; Solenne Chardonnet; Viviane de Almeida Bastos; Manuel Rosa-Calatrava; Antoine Soulé; Amin Emad; Simon Rousseau; et al. (iScience)
Summary: Pre-existing respiratory diseases may influence coronavirus disease (COVID-19) susceptibility and severity. However, the molecular mechanisms underlying the airway epithelial response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection severity in patients with chronic respiratory diseases remain unelucidated. Using an in vitro model of differentiated primary bronchial epithelial cells, we aimed to investigate the molecular mechanisms of SARS-CoV-2 infection in pre-existing cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD). Our study revealed reduced susceptibility of CF and COPD airway epithelia to SARS-CoV-2, relative to that in healthy controls. Mechanistically, reduced transmembrane serine protease 2 (TMPRSS2) activity potentially contributed to this resistance of CF epithelium. Upregulated complement and inflammatory pathways in CF and COPD epithelia potentially primed the antiviral state prior to infection. Analysis of a COVID-19 patient cohort validated our findings, correlating specific inflammatory markers (IP-10, SERPINA1, and CFB) with COVID-19 severity. This study elucidates SARS-CoV-2 pathogenesis and identifies potential biomarkers for clinical monitoring.